Presence Without Adab? A Systematic Review of Augmented and Virtual Reality in Islamic Religious Education and Its Epistemological Alignment with Ta'dīb - Miftahur Rizik S; Dewi Astini; Zul Ikrom; Ali Marwan; Muslimin; Harif Rahman Hakim (Jurnal Ilmu Pendidikan dan Sosial, 2026)
Augmented and virtual reality have entered Islamic religious education faster than the field has developed criteria for judging them. This study reviews 47 empirical and design studies published between 2015 and 2026, retrieved from Scopus, Web of Science, ERIC, DOAJ, and Google Scholar under the PRISMA 2020 protocol. Methodological quality was appraised with the Mixed Methods Appraisal Tool, and every study was coded against a four-dimensional framework derived from the concept of ta'dīb, covering tawḥīdic epistemic framing, the presence of the teacher as murabbī, adab toward sacred content, and internalisation evidenced in enacted practice. Measurement proved heavily skewed toward cognitive achievement, measured in 38 studies, and motivation, measured in 31, while only six studies attempted value internalisation and two addressed adab dispositions. Rigour was thin, since effect sizes appeared in nine studies and delayed post-tests in three. Relational teaching authority was absent from 36 of the 47 studies, several of which presented reduced teacher involvement as an achievement. The review proposes the Ta'dīb-Aligned Immersive Media framework as a design and evaluation instrument for subsequent research.